Botanical Exploration of the Gora Range of the Rajpipla Forests, Gujarat State - Bhatt, R. P.; Bedi, S. J.; Sabnis, S. D. (Indian Forester, 1971)
The present paper is a result of the authors' three years of botanical exploration of the Gora Range of Rajpipla forests. The forests are Mixed Dry Deciduous type with Tectona grandis as the major constituent. In all 460 plant species have been listed, of which 393 belong to dicotyledons, 64 to monocotyledons and 3 belong to pteridophytes.